2021
DOI: 10.7181/acfs.2021.00052
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-type retrobulbar hematoma caused by low temperature after reconstruction of inferior blow-out fracture

Abstract: Retrobulbar hemorrhage is a disastrous condition that can lead to permanent blindness. As such, rapid diagnosis and treatment are critical. Here, we report a patient who presented with retrobulbar hemorrhage following an orbital floor fracture. Restoration of inferior orbital wall with porous polyethylene implant was underwent. Four days after the orbital floor reconstruction, the patient smoked a cigarette outdoors in -3˚C weather. Cold temperature and smoking caused an increase in his systemic blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The forced duction test was performed after implant placement to ensure eye mobility [ 3 ]. Negative pressure drainage systems were not applied, although they are known to be effective for retrobulbar hemorrhage prevention [ 4 ]. In the absence of contraindications, an intravenous injection of 62.5 mg of methylprednisolone was administered once preoperatively and once daily for 2 days postoperatively to control the swelling [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The forced duction test was performed after implant placement to ensure eye mobility [ 3 ]. Negative pressure drainage systems were not applied, although they are known to be effective for retrobulbar hemorrhage prevention [ 4 ]. In the absence of contraindications, an intravenous injection of 62.5 mg of methylprednisolone was administered once preoperatively and once daily for 2 days postoperatively to control the swelling [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…A survey among North American craniomaxillofacial faculty revealed that monitoring for signs and symptoms concerning RBH was the primary reason for admitting patients postoperatively 3 . However, most studies, like ours, have identified either no case or very low rates of RBH, typically <1% 14‐18 . In these studies, the timing of RBH ranged from the immediate postoperative period in the postanesthesia care unit (PACU) to the delayed period of up to 7 days after surgery.…”
Section: Discussionmentioning
confidence: 80%
“…3 However, most studies, like ours, have identified either no case or very low rates of RBH, typically <1%. [14][15][16][17][18] In these studies, the timing of RBH ranged from the immediate postoperative period in the postanesthesia care unit (PACU) to the delayed period of up to 7 days after surgery. A systematic review and meta-analysis found that the onset of RBH was on average 29.8 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%